A study on personal information protection behavior in easy payment service: focused on protection motivation theory - Hoon Shin, Jae; Hyun Choi, Sang (International Journal of Engineering and Technology, 2018)
Background/Objectives: This paper deals with the easy payment service among fin-Tech, a hot market worldwide.'Fintech' refers to a service that combines 'finance' and 'technology' as it is called, or a company that conducts such services.Methods/Statistical analysis: In order to understand the behavior of users of personal information in the simple payment service centered on twenties, I conducted empirical studies using the theory of protection motivation.Findings: The perceived vulnerability of the possibility of personal information infringement and the self - efficacy related to self - confidence of being able to keep personal information were found to have a positive effect on privacy behavior. However, the variables of perceived severity did not have a significant effect on privacy behavior.Improvements/Applications: it is necessary to conduct research on people of various age groups in future research and to carry out research by selecting detailed items within the simple payment service framework.Â